Does Employee Engagement Mediate Performance? Evidence from a Public Sector Agency - Putra, Taufan Eka; Mus, Abdul Rahman; Gani, Achmad; Djamereng, Asdar (International Review of Management and Marketing, 2026)
This study aims to analyze the effects of organizational culture, job satisfaction, and work discipline on employee performance through employee engagement as a mediating variable at the Kotabaru–Batulicin Class II Port Authority. Authority. This study employed a quantitative approach with an explanatory design. The study population consisted of 327 employees, and a census method was used; 273 questionnaires were deemed valid for analysis. Data were collected using a five-point Likert scale questionnaire and analyzed using covariance-based Structural Equation Modeling (SEM) with the assistance of AMOS. Organizational culture, job satisfaction, and work discipline have a positive and significant effect on employee engagement. Job satisfaction and employee engagement have a positive and significant effect on employee performance, whereas organizational culture and work discipline do not have a significant direct effect on performance. Employee engagement was found to fully mediate the effects of organizational culture and work discipline on employee performance, and to partially mediate the effect of job satisfaction on employee performance. The findings emphasize the strategic role of employee engagement in improving employee performance within public sector organizations.